ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI ROTI GORENG MENGGUNAKAN METODE TRADISIONAL DENGAN METODE ACTIVITY BASED COSTING (ABC) PADA UD LAKSANA HATI - Melinawat; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This research was conducted at UD Laksana Hati, having its address at Kp. Kebon Kopi RT. 004 RW. 006 Karang Asih Village, Kec. North Cikarang Bekasi Regency. The purpose of this study was to determine the calculation of the cost of fried bread production using traditional methods carried out by the company and compare it with the method of Activity Based Costing. Data collection techniques used are observation and documentation while the analysis method uses descriptive qualitative analysis. From the results of the research that has been done, it turns out the calculation of the cost of fried bread production using Activity Based Costing method is more accurately used by companies to obtain the desired profit compared to using traditional methods.